2019
DOI: 10.3390/environments6030031
|View full text |Cite
|
Sign up to set email alerts
|

Noise Assessment of Small Vessels for Action Planning in Canal Cities

Abstract: After the European Environmental Noise Directive prescribed noise maps and action plans, wide scientific literature and a consistent number of mitigation strategies emerged for road, railway, airport, and industrial noise. Unfortunately, very little attention has been paid to the noise produced by ports in their surroundings, even though there could be many areas affected by it. At present, more attention seems to be paid to noise produced underwater, mostly for military and security reasons and for its interf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 46 publications
0
29
0
1
Order By: Relevance
“…In fact, knowing the emitting source, is important to avoid noise high noise exposure and noise complaints to citizens living in the nearby of port and avoid the well-known effects compromising people health [24]. In order to prevent these, also in port areas, in the very recent years, studies are growing exploring the noise emitted by ships, with a special focus on fishing vessels [25].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, knowing the emitting source, is important to avoid noise high noise exposure and noise complaints to citizens living in the nearby of port and avoid the well-known effects compromising people health [24]. In order to prevent these, also in port areas, in the very recent years, studies are growing exploring the noise emitted by ships, with a special focus on fishing vessels [25].…”
Section: Introductionmentioning
confidence: 99%
“…Inside the port of Livorno, ARPAT and the Department of Physics of the University of Pisa performed a preliminary study on noise impact generated by recreational craft in the city's internal canals [36]. Through long and short duration pass-by measures, the emissions of two distinct categories of small craft were characterized: recreational craft and small and medium-sized fishing vessels and boats of the police force.…”
Section: Noise Assessment Of Small Vessels For Action Planning In Canmentioning
confidence: 99%
“…To the best of the authors' knowledge, only a few studies have been dedicated to moving ships: Badino et al [53] reported a measurement methodology, Di Bella et al [54] and Fausti et al [55] performed pass-by measurements of cruise ships, while Bernardini et al [56] characterized the sound power level of small vessels moving in channels.…”
Section: Introductionmentioning
confidence: 99%